Magnetic Sphincter Augmentation Outcomes in Severe Gastroesophageal Reflux Disease - Ferrari, Davide; Siboni, Stefano; Riva, Carlo Galdino; Guerrazzi, Guglielmo; Lovece, Andrea; Bonavina, Luigi (Frontiers in Medicine, 2021)
Introduction: Outcomes of laparoscopic procedures for gastroesophageal reflux disease (GERD) are variable depending on surgical expertise and/or patient-related factors. Some procedures may be inadequate in patients with severe disease. Effectiveness of laparoscopic magnetic sphincter augmentation (MSA) has not been extensively tested in patients with severe disease. Methods: A prospectively collected database was analyzed to identify patients who underwent MSA at a single institution. Individuals who had previous esophago-gastric surgery were excluded. Severe GERD was defined as lower esophageal sphincter pressure <5 mmHg, distal esophageal amplitude <30 mmHg, Barrett's metaplasia, stricture or grade C-D esophagitis, and/or DeMeester score >50. Clinical characteristics and outcomes of patients with severe GERD were compared with those of patients with mild to moderate GERD who served as control group. Results: Over the study period, a total of 336 patients met the inclusion criteria, and 102 (30.4%) had severe GERD. The median follow-up was 24 months (IQR = 75) in severe GERD patients and 32 months (IQR = 84) in those with non-severe GERD. Patients with severe GERD had a higher rate of dysphagia and higher GERD-HRQL scores. After the MSA procedure, symptoms, health-related quality of life scores, and proton-pump inhibitors consumption significantly decreased in both groups (p < 0.05). No difference between groups was found in the prevalence of severe post-operative dysphagia, the need for endoscopic dilation or device removal, and the DeMeester score. Conclusion: Laparoscopic MSA is safe and effective in reducing symptoms, PPI use, and esophageal acid exposure also in patients with severe GERD.